(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Communication has a very important role to play in today’s competitive world. Communication has become an integral part of the growth, performance and profitability of any company. This is the software that gives the power to communicate anywhere, anytime, to a person. Due to advances in technology, communication is now becoming easier and faster. The Indian broadband and telecommunications industry is growing rapidly and will make a significant contribution to India’s GDP. The present work is to analyze the level of customer satisfaction with BSNL and Reliance Fiber to Home Services in Bhopal (M.P.). Using a company survey, the primary data was collected. The study also addresses the FTTH service provider’s measurement of their customer experience. Tariff rates, interconnectivity, browsing speed, value-added services, voice services are some of the parameters considered for research.